(untitled) (Academicia Globe: Inderscience Research, 2023)
In this article, the role of innate ability and talent is important in the development of the intellectual potential of primary school students. Our young people, who have innate abilities, quickly learn all the educational, educational and professional teachings of adults and can quickly master them and apply them to life. But not all our young people are gifted with this ability and talent. Therefore, it is primarily the responsibility of our pedagogues and the general public, families, neighborhoods, and educational institutions, to develop skills and improve the talents of young people. Children’s innate abilities for various activities were discussed in the team, on their own work.